Bioactivity of PEGylated Graphene Oxide Nanoparticles Combined with Near-Infrared Laser Irradiation Studied in Colorectal Carcinoma Cells - Natalia Krasteva (MDPI AG, 2021)
Central focus in modern anticancer nanosystems is given to certain types of nanomaterials such as graphene oxide (GO). Its functionalization with polyethylene glycol (PEG) demonstrates high delivery efficiency and controllable release of proteins, bioimaging agents, chemotherapeutics and anticancer drugs. GO–PEG has a good biological safety profile, exhibits high NIR absorbance and capacity in photothermal treatment. To investigate the bioactivity of PEGylated GO NPs in combination with NIR irradiation on colorectal cancer cells we conducted experiments that aim to reveal the molecular mechanisms of action of this nanocarrier, combined with near-infrared light (NIR) on the high invasive Colon26 and the low invasive HT29 colon cancer cell lines. During reaching cancer cells the phototoxicity of GO–PEG is modulated by NIR laser irradiation. We observed that PEGylation of GO nanoparticles has well-pronounced biocompatibility toward colorectal carcinoma cells, besides their different malignant potential and treatment times. This biocompatibility is potentiated when GO–PEG treatment is combined with NIR irradiation, especially for cells cultured and treated for 24 h. The tested bioactivity of GO–PEG in combination with NIR irradiation induced little to no damages in DNA and did not influence the mitochondrial activity. Our findings demonstrate the potential of GO–PEG-based photoactivity as a nanosystem for colorectal cancer treatment.